EFEKTIVITAS PENDIDIKAN GIZI DENGAN APLIKASI BERBASIS ANDROID TERHADAP PENGETAHUAN SERTA KONSUMSI SAYUR DAN BUAH REMAJA - Salsabilla Fauziah; Surmita Surmita; Witri Priawantiputri; Mira Mutiyani; Umi Mahmudah; Gurid Mulyo (Jurusan Gizi Poltekkes Kemenkes Bandung, 2023)
One of many eating behavior problems is the lack of vegetables and fruit consumption. The lack of knowledge decrease personal ability in implementing the nutritional information in daily life. Nutrition Education is one of the effort to overcome the vegetable and fruit consumption problem. This study aims to see the effect of Nutrition Education using Android based application